A novel approach for coordinated operation of variable speed wind energy conversion in smart grid applications. (July 2019) - Ahuja, Hemant; Kumar, Pawan
Abstract: In smart grid applications, the high penetration level of wind energy requires precise coordination of wind energy conversion systems (WECS) with the existing grid. In this paper, a variable speed WECS using Squirrel-Cage Induction Generator (SCIG) is modeled and analyzed under fault conditions. The converters and their controllers are so designed that the complete system works in coordination and the turbine remains operative even under fault conditions. A droop controller regulates the torque and generator speed to limit power generation during faults, thereby preventing a shutdown of the wind turbine. A dual current controller is designed for individual control of positive and negative sequence currents to eliminate the double frequency oscillations that arise at the DC-link voltage during unsymmetrical faults. With the proposed controller, rise in DC link voltage and generator speed is limited to a bounded value of 1.2 pu whereas the fault current is limited to 1.5 pu.